NORSE/FIRES: how can we advance our understanding of this devastating condition? - Champsas, Dimitrios; Zhang, Xushuo; Rosch, Richard; Ioannidou, Evangelia; Gilmour, Kimberly; Cooray, Gerald; Woodhall, Gavin; Pujar, Suresh; Kaliakatsos, Marios; Wright, Sukhvir K. (Frontiers in Neurology, 2024)
New onset refractory status epilepticus (NORSE) is a rare and devastating condition characterised by the sudden onset of refractory status epilepticus (RSE) without an identifiable acute or active structural, toxic, or metabolic cause in an individual without a pre-existing diagnosis of epilepsy.Febrile infection-related epilepsy syndrome (FIRES) is considered a subcategory of NORSE and presents following a febrile illness prior to seizure onset. NORSE/FIRES is associated with high morbidity and mortality in children and adults.In this review we first briefly summarise the reported clinical, paraclinical, treatment and outcome data in the literature. We then report on existing knowledge of the underlying pathophysiology in relation to in vitro and in vivo pre-clinical seizure and epilepsy models of potential relevance to NORSE/FIRES and propose future directions for research.